Health is economy: Some lessons from COVID-19 - Ernesto M. Pernia (University of the Philippines, School of Economics (UPSE), 2020)
"Health is wealth", though a cliché, has scarcely been uttered during this coronavirus pandemic. Not surprising as it has become second nature to individuals, while what we have is a public health crisis. So more appropriate is "health is economy." Indeed, health and economy are intimately linked and interactive - sound public health is good for the productivity and sustainability of the economy which, in turn, generates jobs and goods needed for a healthy population.
Keywords: 330; COVID-19; Philippine economy; Philippines